The Effects of Fecal Donors with Different Feeding Patterns on Diarrhea in a Patient Undergoing Hematopoietic Stem Cell Transplantation - Jianping Zhang; Guangxu Ren; Minghua Li; Peihua Lu; Suqin Yi (Case Reports in Hematology)
Almost 90% of patients undergoing hematopoietic stem cell transplantation (HSCT) experience diarrheal episodes, which represent a severe, often life-threatening complication for these patients. Although fecal microbiota transplantation (FMT) represents an alternative treatment option for infection-related diarrhea, the application of FMT in HSCT patients is greatly restricted for safety reasons. Furthermore, the therapeutic outcomes of FMT as a diarrhea treatment are somewhat related to the choice of the FMT donor. Here, we comprehensively profiled the dynamic changes in the intestinal microbiota after FMT from two donors with different feeding patterns and the same severely diarrheal recipient undergoing HSCT via a 45-day clinical observation. Importantly, no adverse events attributed to FMT were observed. The stool volume and frequency of the patient were reduced when we used feces from donor #1 (mixed feeding), but these changes were not observed after FMT from donor #2 (exclusive breastfeeding). Interestingly, no obvious differences in overall diversity (Shannon) or richness (Chao1) between the two donors were observed. Additionally, Bifidobacterium accounted for 29.9% and 18.1% of OTUs in the stools of donors #1 and #2, respectively. Lactobacillus accounted for 16.3% and 2.9% of the stools of donors #1 and #2, respectively. Furthermore, through longitudinal monitoring of the patient, we identified 6 OTUs that were particularly sensitive to the different FMT complements. Together, we present a case report suggesting that the overall diversity of the intestinal microbiota may not be the only important element in the selection of an effective FMT donor.